Wordsworth and the Cultivation of Women. - Page, Judith W. (University of California Press, 2022)
Focusing on the poems of Wordsworth's ""Great Decade,"" feminist critics have tended to see Wordsworth as an exploiter of women and ""feminine"" perspectives. In this original and provocative book, Judith Page examines works from throughout Wordsworth's long career to offer a more nuanced feminist account of the poet's values. She asks questions about Wordsworth and women from the point of view of the women themselves and of eighteenth- and nineteenth-century.
Description based upon print version of record.
Keywords: Wordsworth, William, -- 1770-1850.; Feminism and literature -- England -- History -- 19th century.; Women and literature -- England -- History -- 19th century.; Feminist poetry, English -- History and criticism.